Tyrosinase Inhibition from Green Tea (Camellia sinensis (L.) Kuntze) gel - Hanifah Rahmi; Supandi Supandi; Naniek Setiadi Radjab; Tiara Julianti (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
Green tea (Camellia sinensis (L.) Kuntze) leaf has polyphenol substance that able to inhibit tyrosinase enzyme. Tyrosinase enzyme is one of the essential components that can be initiated melanin formation on the skin (melanogenesis). The natural inhibitory enzyme can be utilized in cosmetics and medicinal industries as depigmentation agent. Green tea leaf was formulated in the dosage form of a gel with carbomer 934 as a gelling agent. This study aimed to determine the optimum concentration of carbomer 934 on green tea leaf extract gel that has an inhibitory tyrosinase activity. This research used three carbomer 934 concentration, there was 0.5%, 0.75%, and 1% respectively. Which every formula was evaluated during six weeks involve organoleptic, homogeneity, viscosity, pH, centrifuge, and freeze-thaw test (during six cycles). The optimum formula was evaluated tyrosinase activity used a spectrophotometer-vis. The results showed that the great concentration of carbomer 934 was contained on the first formula, which has not phase separation and 49.62 ppm of IC50 value. This research showed that green tea leaf extract gel with 0,5% carbomer 934 prevented tyrosinase activity. Keywords: Carbomer 934, gel, green tea leaf extract, inhibitory of tyrosinase